ANALISIS SIKAP APOTEKER TERHADAP PERATURAN PEMERINTAH NO. 51/2009 TENTANG PEKERJAAN KEFARMASIAN (STUDI KASUS DI APOTEK KOTA PALEMBANG) - , Rastria Meilanda, Prof. Dr. Achmad Fudholi, DEA, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Pharmacist holds authority on professionalism in performing pharmacy work. That authority provides definite legitimacy for pharmacist profession in performing her/his function and roles within health domain to achieve pharmacy service standard, particularly in medicine services at pharmacy-store listed in Government Regulation (PP) No. 51/2009 concerning pharmacy occupation. These function and rule should be indicated within attitude and behave as pharmacist. Attitude and behavior are strongly determines pharmacistâ responsibility and service. Presents research is expected provides foundation for pharmacist attitude and behavior in facing PP No. 51/2009. It providing description of pharmacist readiness in Palembang City in implementing above regulation thus the objectives of pharmacy service standard can be achieved. This is descriptive research, data were gained using questioner. Pharmacist attitude were classified into three dimensions named cognitive, affective and cognation dimensions. Samples were selected employed random sampling method by giving questioner titled pharmacist attitude in facing PP No. 51/2009. Collected data were followed by validation and reliability test, then been analyzed to obtain research outcome. Research outcome reveals that most pharmacists in Palembang City has acknowledged and well-understand over PP No.51/2009. They also perceived content and, thus, raise positive attitude and inclined to behave according to the regulation. However, pharmacist who disagree with PP No. 51/2009 since perceives difficult to implement it do not sentenced any sanction both from organization and government, generally this caused by limited knowledge gain by pharmacist.